Outside options: another reason to choose the first-price auction - Oliver Kirchkamp; Eva Poen; J. Philipp Reiss (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
In this paper we study equilibrium- and experimental bidding behaviour in first-price and second price auctions with outside options. We find that bidders do respond to outside options and to variations of common knowledge about competitors outside options. However, overbidding in first-price auctions is significantly higher with outside options than without. First-price auctions yield more revenue than second-price auctions. This revenue-premium is significantly higher with outside options. In second-price auctions the introduction of outside options has only a small effect.
Keywords: 330; Auktionstheorie; Test; Theorie